Analysis of Solaria Brand Dispute Resolution with Solaris (Case Study No. 775 K/PDT.SUS-HKI/2021) - Simbolon, Alum; Cindy, Cindy (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research discusses the dispute between the SOLARIA and SOLARIS brands in Indonesia, focusing on Decision No. 775 K/Pdt.Sus-HKI/2021. It aims to analyze the considerations of the Panel of Judges in resolving the trademark dispute and determine the protection of the SOLARIA brand against the SOLARIS brand in the mentioned decision. The findings reveal that the Plaintiff, as the owner of the SOLARIA brand, is the registrant and first user of the brand under the first-to-file system. Consequently, the Plaintiff is the legal owner of the SOLARIA brand, which is recognized as a well-known brand based on registrations in various countries. The Defendant's registration of the SOLARIS mark is considered to be in bad faith due to significant similarities in terms of shape, sound, and pronunciation. This suggests that the Defendant registered the mark solely for their own business interests, misleading consumers and causing harm to other parties. Accordingly, the Directorate General of Intellectual Property should reject the Defendant's SOLARIS trademark application under Article 21 paragraph (1) letter a of the MIG Law. The Plaintiff, as the owner of the SOLARIA brand, obtains legal protection through the resolution of this case via a legal process. The Panel of Judges granted the Plaintiff's lawsuit and declared the SOLARIS brand invalid according to the law. The cassation request submitted by the Defendant was also rejected, providing repressive legal protection for the Plaintiff.